Answer:
Explanation:
f(x) = 5x-4
1. First, you want to rewrite the function with x and y
y= 5x-4
2. Then, switch the variables x and y
x= 5y-4
3. Now, solve for y.
x= 5y-4
x+4 = 5y
--> This is your inverse.
To check:
You can check this answer by plugging your inverse into your original function. You will know that your inverse is correct if your answer is x = 1
1. y= 5x-4,
![y = (1)/(5) x + (4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vvob8tppourebra7t49yg1f3qulehfcxne.png)
2. Since they both equal to y, pick one equation to plug into the other. In this case, you are simply setting them equal to each other.
5x-4 =
![(1)/(5) x +(4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9i3a6e6aat5dt7btlie61ezmhwo9qil2de.png)
3. Solve for x.
5x-4 =
![(1)/(5) x +(4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9i3a6e6aat5dt7btlie61ezmhwo9qil2de.png)
![(4)/(5)+4 = 5x - (1)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zjz2jxw0nde2p217itsnhgu42hqi2d4sll.png)
24=24x
x=1
4. Since you reached the answer x=1, you didn't get any extraneous solutions and your answer is therefore correct.